BIOGRAPHICAL NOVELS S. PROTSYUK IN AN INTERTEXTUAL DIMENSION - Chernysh, A. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article is devoted to the main markers of intertextuality in the novels of S. Protsyuk «The Rose of a Ritual Pain» and «Masks Falling Slowly» and their functioning in the text plane of the work. The intertextual potential of S. Protsyuk’s biographical novels manifests itself in the archetychtuality that manifests itself in the mixing of genre codes (artistic biography, epistolary, memoirs, essays), and the actual intertextuality claimed mainly by ancient Greek myths and mythologems (Cassandra, Dionysus, Ariadne, Orpheus, Eternal Woman, Eve, Sisyphus, Scylla and Charybda, the Trojan Kingdom), as well as sleepy myths, representing a powerful dream space. Artistically built in the structure of works images of ancient Greek mythology contribute to the assimilation of the tragic world perception of the heroes (Kassandra – Vasyl Stefanyk), hedonistic and idealized conception of life creation (Dionysus – Volodymyr Vynnychenko, Orpheus – Volodymyr Vynnychenko), risky and adventurous lifestyle (between Scylla and Kharybda) etc. The names of famous artists and politicians (Grygoriy Skovoroda, Confucius, Seneca, Neron, Nietzsche, Baudelaire, Maupassant, Hitler, Stalin) have been introduced into the text plane of the novel «The Rose of a Ritual Pain», explaining in most cases the way of thinking, perception and understanding, as well as the creative manner, intellectual and spiritual development of Volodymyr Vynnychenko. The method of color matching used by S. Protsyuk senses the intertextual background of the novel about Vasyl Stefanyk, combined with quotations from Ukrainian folk songs. Much attention in the novel «Rose of a Ritual Pain» is paid to the existential motives of the work, distinguishing the key category of choice. The archetype of Mother, expressed in the novel about Vasyl Stefanyk, reinforces the intertextual potential of the work, distinguishing motives of grief, amount, loss.